Effect of a Low Carbohydrate Diet on Weight Loss in Obese Patients: Meta-Analysis - Sisilia Prima Yanuaria Buka; Dito Anurogo; Nur Hasanah; Jeane L.I. Sumarauw; Muntasir Muntasir (Journal of World Future Medicine, Health and Nursing, 2024)
Obesity is a rapidly increasing global health problem and requires effective intervention strategies. Low-carbohydrate diets have become a major concern in obesity management, but previous studies have provided mixed results. This study aims to conduct a meta-analysis to evaluate the effect of a low-carbohydrate diet on weight loss in obese patients. The research method used in this research is meta analysis. A literature search was conducted through electronic databases for studies that met the inclusion criteria. Data from selected studies were then analyzed using meta-analysis methods to determine the effects of low-carbohydrate diets on weight loss. The results of this study stated that the meta-analysis involved data from 10 studies that met the inclusion criteria. The results showed that a low-carbohydrate diet significantly contributed to weight loss in obese patients. The average weight loss achieved was significantly higher in the group on a low-carbohydrate diet compared to the control group. The conclusion of this study, namely from this meta-analysis, shows that a low-carbohydrate diet is effective in reducing weight in obese patients. The clinical implication of these results is that low-carbohydrate diets may be an effective therapeutic option in the management of obesity. However, further research needs to be done to understand in more depth the long-term effects and safety of this low-carbohydrate diet. Through this research, it is hoped that it can provide a deeper understanding of the effectiveness of a low-carbohydrate diet as an obesity management strategy.